A Case of Giant Intracranial Tuberculoma in an Infant: Clinical and Radiologic Pitfalls. (March 2015) - Raheja, Amol; Sinha, Sumit; Sable, Mukund Namdev; Sharma, Mehar Chand; Sharma, Bhawani Shankar
Intracranial tuberculoma in infants are a rare occurrence. We report a 7-month-old male infant presenting to our tertiary care referral center with complaints of global developmental delay and right hemiparesis for 3 months. Radiologic imaging was suggestive of large left frontoinsular space–occupying lesion with initial differential of primitive neuroectodermal tumor or desmoplastic infantile ganglioglioma. Considering the clinicoradiologic findings and no history suggestive of immunodeficiency or contact with tuberculosis, surgical decompression was done. Final histopathology revealed multiple epithelioid granulomas suggestive of tubercular etiology or intracranial Langerhans cell histiocytosis. He was started on antitubercular therapy after ruling out Langerhans cell histiocytosis using CD1a and Langerin immunohistochemistry staining. Interpretation of tuberculous etiology in infants can be challenging for clinicians, radiologists, and pathologists. A high index of suspicion is necessary to diagnose such lesions, predominantly in endemic regions.